A HYBRID MCDM METHOD TO IDENTIFY CRITICAL FACTORS OF FOREIGN DIRECT INVESTMENT - Chang, Tien-Hsiang; Yeh, Wen-Chin; Fu, Hsin-Pin; Teng, Ying-Hua (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
The purpose of this study was to understand the varied importance of critical factors (CFs) that affect foreign direct investment (FDI) and optimize the allocation of limited resources to the CFs to increase chances for international business success. We used eclectic theory as a framework. The fuzzy analytic hierarchy process (FAHP) and the concept of the Vlse Kriterijumska Optimizacija Kompromisno Resenje (VIKOR) acceptable advantage were used to obtain the weights of the CFs and to identify the CFs objectively. Sensitivity analysis was performed to optimize the CFs. With the derivation of the CF weights, Taiwanese catering firms (i.e., the focal sample) can improve the allocation of their resources to the CFs to reduce the risk of FDI failure. Management implications, factor path analysis, and study contributions are also discussed.